Bede's rhetorical use of dating formulas in the Historia ecclesiastica. (26th April 2019) - Shaw, Richard
Abstract: Bede frequently used dating formulas to frame his narrative. In some cases these simply reflect the wording of his sources, whether he states that he is quoting from them or not. More often, however, the types of phrasing he uses reflect conscious construction on his part. Such formulas drew attention to key people and passages in the work and so assisted in the achievement of Bede's authorial intentions in the Historia ecclesiastica . These phrases also imitated and developed previous exemplars from earlier historiography thus enabling Bede to situate and validate his work within the genre.